Biocomputing 2015 2014
DOI: 10.1142/9789814644730_0030
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Search Behavior of Healthcare Professionals for Drug Safety Surveillance

Abstract: Post-market drug safety surveillance is hugely important and is a significant challenge despite the existence of adverse event (AE) reporting systems. Here we describe a preliminary analysis of search logs from healthcare professionals as a source for detecting adverse drug events. We annotate search log query terms with biomedical terminologies for drugs and events, and then perform a statistical analysis to identify associations among drugs and events within search sessions. We evaluate our approach using tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…A second study demonstrated that combining data from the FDA Adverse Event Reporting System (FAERS) with consumer search logs improved accuracy of adverse drug event detection by 19%, compared with using either source alone [ 16 ]. Our findings in this work and in a recent preliminary study [ 33 ] indicate that incorporating search logs of health care professionals for pharmacovigilance is a promising approach.…”
Section: Discussionsupporting
confidence: 52%
“…A second study demonstrated that combining data from the FDA Adverse Event Reporting System (FAERS) with consumer search logs improved accuracy of adverse drug event detection by 19%, compared with using either source alone [ 16 ]. Our findings in this work and in a recent preliminary study [ 33 ] indicate that incorporating search logs of health care professionals for pharmacovigilance is a promising approach.…”
Section: Discussionsupporting
confidence: 52%
“…Pharmacovigilance refers to the science relating to the detection, assessment, understanding and prevention of adverse effects or any other drug-related problem. The Council for International Organizations of Medical Sciences (CIOMS) defines a safety signal as ‘information that arises from one or multiple sources (including observations or experiments), which suggests a new, potentially causal association, or a new aspect of a known association between an intervention [e.g., administration of a medicine] and an event or set of related events, either adverse or beneficial, that is judged to be of sufficient likelihood to justify verificatory action.’ Efficient and reliable identification and evaluation of ‘safety signals’ requires access to evidence from disparate sources, including electronic health records 3–6 , spontaneous reporting systems (SRS) 7–9 , social media 10–14 , literature mining 15–18 , web search queries via search engine logs 19–22 , and biological and chemical knowledge bases 23–25 . The belief is that each data source provides a unique vantage point in understanding a drug’s safety profile.…”
Section: Background and Summarymentioning
confidence: 99%
“…The use of social media/web data for ADR monitoring, including assessment of search logs from healthcare professionals [22], is receiving increasing levels of attention [23]. The amount of user-generated data on social media and other Internet-based venues provides the possibility to systematically mine, aggregate, and analyze textual/unstructured data (e.g.…”
Section: Role Of Post-marketing Multiple Sources/social Media Surveysmentioning
confidence: 99%